Convergence of Variational Iteration Method for Second-Order Delay Differential Equations - Hongliang Liu; Aiguo Xiao; Lihong Su (Journal of Applied Mathematics)
This paper employs the variational iteration method to obtain analytical solutions of second-order delay differential equations. The corresponding convergence results are obtained, and an effective technique for choosing a reasonable Lagrange multiplier is designed in the solving process. Moreover, some illustrative examples are given to show the efficiency of this method.